Financing social ventures by crowdfunding: the influence of entrepreneurs’ personality traits - Bernardino, Susana (2015)
Purpose – This research aims to understand the role played by social entrepreneurs’ personality traits on the choice between the traditional donation model and social crowdfunding (CF) to finance social projects. Design/methodology/approach – Social CF is examined as an instrument to capture funds for social projects, and the particular case of the Portuguese Social Stock Exchange (PSSE) is presented. The approach is quantitative in nature and the data were collected through a questionnaire that was emailed to non-governmental organizations in Portugal and founders of the projects listed on PSSE. Logistic regression was employed to predict the probability that a social entrepreneur would use PSSE rather than traditional financing. The predictor variables were based on the big five personality traits. Findings – Our investigation reveals that the agreeableness and neuroticism factors were not even considered in the results of the factorial analysis, which indicates the minor importance of these personality traits in the funding decisions of the Portuguese social entrepreneurs. The same applies to the factors of openness to new experiences and extraversion, which, although considered in the logistic analysis, showed no statistical significance. Finally, the conscientiousness personality trait seems to be the only factor that might explain the use of the PSSE platform. Originality/value – Studies on the profile of the social entrepreneurs that use CF for financing social projects are relatively rare, specifically in the context of Social Stock Exchange platforms. Additionally, there is a need to carry out more empirical evidence about the effect of social entrepreneurs’ personality traits on the decision to finance social projects through social CF platforms vis-a-vis the traditional donation model.